Strategic governance of decentralized construction portfolios: optimization of asynchronous stages in scalable retail environments - Tymoshenko, Andrii (Global Prosperity, 2026)
Abstract. The article examines the strategic scaling of construction portfolios from 10 to 54 concurrent projects. Based on a decade of empirical data, the study substantiates how the VFRP methodology allows for a 440% increase in operational volume (from 8 to 54 units per year) without increasing the administrative error rate. The VFRP methodology allows for a significant increase in operational volume (scaling from 10 to 54 units annually, as demonstrated in the UniCredit Bank case during 2006-2007) without increasing the administrative error rate. The author analyzes systemic challenges associated with operational stage asynchronicity and informational entropy, which, when utilizing traditional linear scheduling methods (CPM), lead to schedule variances ranging from 5-20% and a cascaded escalation of rework costs. As a solution, the proprietary VFRP technology is presented, predicated on establishing the axiological priority of the asset`s final visual state over intermediate processes. A pivotal element of the methodology is the inverse scheduling algorithm relative to the Grand opening date, integrated with a system of hard milestones and the implementation of visual heuristics via specialized Contractor`s Visual Manuals. Empirical verification of the technology corroborates near-zero schedule variance, no statistically significant schedule deviation, practically eliminating incremental rent costs. It is demonstrated that the system maintains robust efficacy while concurrently managing a portfolio of up to 20 asynchronous assets. The research findings establish a scientifically grounded framework for scaling retail management systems without compromising control quality, ensuring precision in ROI forecasting.